32. THE DIETARY STATUS OF CHILDREN UNDER 24 MONTHS WITH PNEUMONIA TREATED INPATIENT AT THE NATIONAL CHILDREN’S HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the dietary intake of children under 24 months with pneumonia treated at the National Children’s Hospital in 2023 and propose effective nutritional interventions.Method: A cross-sectional study was conducted on 200 children aged 1-23 months at the Respiratory Center from June to November 2023. Dietary intake was assessed using 24-hour recall, analyzed for energy and nutrients based on the 2017 Vietnam food composition table, and compared with recommended dietary allowances (RDA).Results: Prevalence of undernutrition was 19.5% (underweight), 19% (stunting), and 17.5% (wasting). Most nutrients had low RDA compliance: energy (22.1%), carbohydrates (6.9%), lipids (45.4%), vitamin A (5.8%), vitamin D (4.6%), and zinc (0%). Only protein (87.2%) and B vitamins (B1: 73.3%; B2: 90.7%) showed good compliance. No significant dietary differences were found between undernourished and non-undernourished children.Conclusion: The dietary intake of children under 24 months with pneumonia at the National Children’s Hospital in 2023 was severely deficient in energy, carbohydrates, lipids, vitamins A and D, and zinc, necessitating urgent nutritional interventions to improve nutritional status and support treatment.
Keywords: Pneumonia; children; dietary intake; undernutrition; inpatient.